Răspuns :
l----------l primul }
l----------l-l+2 al doilea } 69 suma
l----------l-l-l+2+2 al treilea }
2+2+2=6 (ce este în plus)
1+1+1=3 segmente egale
69-6=63 (3 segmente egale)
63:3=21 primul
21+2=23 al doilea
21+2+2=25 al treilea
predecesori
21-1=20
23-1=22
25-1=24
l----------l-l+2 al doilea } 69 suma
l----------l-l-l+2+2 al treilea }
2+2+2=6 (ce este în plus)
1+1+1=3 segmente egale
69-6=63 (3 segmente egale)
63:3=21 primul
21+2=23 al doilea
21+2+2=25 al treilea
predecesori
21-1=20
23-1=22
25-1=24